Non-Linear Mappings and their Applications - Darina Stachova (Communications - Scientific letters of the University of Zilina, 2014)
In this contribution we discuss selected geometrical mappings that, although uncommon in practice, are important and irreplaceable in some areas of engineering, architecture and art (scenography, embossing, panoramic cinematography).